Combination therapy of thiamine, vitamin C and hydrocortisone in treating patients with sepsis and septic shock: a meta-analysis and trial sequential analysis. Issue 1 (6th December 2021) - Yao, Renqi; Zhu, Yibing; Yu, Yue; Li, Zhixuan; Wang, Lixue; Zheng, Liyu; Li, Jingyan; Huang, Huibin; Wu, Guosheng; Zhu, Feng; Xia, Zhaofan; Ren, Chao; et al.
Abstract: Background: The objective of this study was to evaluate the clinical efficacy of thiamine and vitamin C with or without hydrocortisone coadministration on the treatment of sepsis and septic shock. Methods: MEDLINE, EMBASE and CENTRAL databases were searched for randomized controlled trials (RCTs) that made a comparative study between the combination therapy of vitamin C and thiamine with or without hydrocortisone and the administration of placebo in patients with sepsis or septic shock. Two reviewers independently performed study selection, data extraction and quality assessment. Both short-term mortality and change in the sequential organ failure assessment (SOFA) score from baseline (delta SOFA) were set as the primary outcomes. Secondary endpoints included intensive care unit (ICU) mortality, new onset of acute kidney injury, total adverse events, ICU and hospital length of stay, duration of vasopressor usage and ventilator-free days. Meanwhile, trial sequential analysis was conducted for primary outcomes. Results: Eight RCTs with 1428 patients were included in the current study. The results showed no significant reduction of short-term mortality in sepsis and septic shock patients who received combination therapy of vitamin C and thiamine with or without hydrocortisone compared to those with placebo {risk ratio (RR), 1.02 [95% confidence interval (CI), 0.87 to 1.20], p  = 0.81, I 2  = 0%; risk difference (RD), 0 [95% CI, −0.04 to 0.05]}. Nevertheless, the combination therapy was associated with significant reduction in SOFA score [mean difference (MD), −0.63, (95% CI, −0.96 to −0.29, p  < 0.001, I 2  = 0%] and vasopressors duration (MD, −22.11 [95% CI, −30.46 to −13.77], p  < 0.001, I 2  = 6%). Additionally, there were no statistical differences in the pooled estimate for other outcomes. Conclusions: In the current meta-analysis, the combination therapy of vitamin C and thiamine, with or without hydrocortisone had no impact on short-term mortality when compared with placebo, but was associated with significant reduction in SOFA score among patients with sepsis and septic shock.